2018
DOI: 10.1142/s0192415x18500787
|View full text |Cite
|
Sign up to set email alerts
|

Activity Dependent Mammalian Target of Rapamycin Pathway and Brain Derived Neurotrophic Factor Release is Required for the Rapid Antidepressant Effects of Puerarin

Abstract: Puerarin is a traditional Chinese medicine with beneficial effects of reduced depression-like behaviors in mice with stress. Previous studies also show that puerarin can produce neuroprotective effect via activating the Akt or increased brain-derived neurotrophic factor (BDNF) expression. Interestingly, BDNF and Akt downstream target, mammalian target of rapamycin (mTOR) mediate the fast-acting antidepressant properties of ketamine. Until now, the involvement of the mTOR signaling pathway or BDNF on puerarin-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Recently, Puerarin has been reported to activate AMPA receptors-induced mTOR signaling pathway, increase BDNF release, as well as increase GluR1 phosphorylation at its PKA site and facilitate AMPA receptors membrane insertion. These effects seem to suggest that it may be potentially used for the treatment of depression [ 102 ]. Total saikosaponins is the major ingredient of Bupleurum yinchowense .…”
Section: Regulation Of Glutamate-mediated Signaling By the Natural Comentioning
confidence: 99%
“…Recently, Puerarin has been reported to activate AMPA receptors-induced mTOR signaling pathway, increase BDNF release, as well as increase GluR1 phosphorylation at its PKA site and facilitate AMPA receptors membrane insertion. These effects seem to suggest that it may be potentially used for the treatment of depression [ 102 ]. Total saikosaponins is the major ingredient of Bupleurum yinchowense .…”
Section: Regulation Of Glutamate-mediated Signaling By the Natural Comentioning
confidence: 99%
“…Similarly, it has also been shown that puerarin ameliorated ovariectomy-induced depressive-like behavior possibly through enhancing neurogenesis in the dentate gyrus of the hippocampus, and upregulating BDNF and the transcription of various estrogen receptors (ERα and ERβ) [ 102 ]. Similarly, activation ofα-amino-3-hydroxy-5-methylisoxazole-4-propionic acid receptors (AMPAR)/ mTOR signaling, together with an increased release of BDNF [ 103 ], upregulation of BDNF and activation of ERK signaling in the prefrontal cortex in diabetic rats [ 104 ], contributed to the anti-depressive effects of puerarin.…”
Section: Bioactivity Of Puerarin In Central Nervous System Disordersmentioning
confidence: 99%
“…99,[102][103][104] Among them, saikosaponins a-d, quercetin, rutin, puerarin, (2Z,8Z/E,10E)-pentadecatriene-4,6-diyne-1-ol and (2Z,8Z/E,10E)-heptadecatriene-4,6-diyne-1-ol have been reported to be the active antidepressant constituents of Bupleuri Radix. 99,[104][105][106] Taken together, the antidepressant activities of Bupleuri Radix have been elucidated in several experimental models, but the underlying mechanisms of its antidepressant effects and the active metabolites are largely unknown and need future investigation.…”
Section: Bupleuri Radixmentioning
confidence: 99%
“…As the consequence of this activation, a significant increase in GluR1 phosphorylation at its PKA site and BDNF released were promoted to exert antidepressant effects on experimental animals. 105…”
Section: Puerarinmentioning
confidence: 99%